Actualization of Non-Verbal Communication Aspects in the Works of O. Potebnya in Focus of Ukrainian Live Speech (Based on the Illustrations from S. Rudansky’s Poetic Discourse) - Осіпова, Тетяна Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The scientific heritage of O. Potebnia contains the origins of the modern theory of non-verbal communication. In the system of the scientist’s linguistic views the main parameters of non-verbal communication are highlighted and characterized in terms of their origin, formation and development, role in the language ontology. The article considers the parameters of non-verbal communication based on the actualization of the system of human sense organs that can act together producing peculiar images, stirring imagination, language ornament patterns, modelling a relevant linguistic worldview. S. Rudansky’s tall tales reflect Ukranian live speech, they are an important source, in particular of the national spirit reconstruction and the specific character of using non-verbal means of communication.